WHEN YOU'RE A VAM-WOLF-ZOM . - Banks, Steven (MIDDLE SCHOOL BITES, 2020)
Eleven-year-old Tom Marks has big plans for middle school, but the day before classes begin he is bitten by a vampire, a werewolf, and a zombie.